Background to the Nature of International Migration in the African Continent and Zimbabwe - Winniefridah Matsa (Springer, Cham, 2023)
The opening chapter provides the background on the trends and the nature of migration globally, the African continent, Southern Africa and Zimbabwe as the context of the problem of international migration, marginality and education. The context and reasons provide for the intricate linkage between marginality, migration and education. The phases (waves) of migration and theoretical perspectives underpinning causes of international migration in Zimbabwe are also discussed. International migration dates back to historical contexts, colonialism, cultural ways of life (nomadism), war and conflict and displacement although the book focuses on labour migration as an alternative livelihood in Zimbabwe. International migration has become a topical issue worldwide. Initially, migration was selective in terms of gender or age group, but it has since broadened to include all genders and age groups, legal and illegal migrants, educated and uneducated, skilled and unskilled, married and unmarried. With globalisation and improved modes of transport, migration is open to everyone. The nature and trends of migration at micro levels as Bulilima and Mangwe mirror those of Southern Africa, the African continent and the international world.